Sofosbuvir-Daclatasvir-Simeprevir Plus Ribavirin in Direct-Acting Antiviral–Experienced Patients With Hepatitis C. (10th March 2017) - Hézode, Christophe; Fourati, Slim; Chevaliez, Stéphane; Scoazec, Giovanna; Soulier, Alexandre; Varaut, Anne; François, Murielle; Ruiz, Isaac; Roudot-Thoraval, Françoise; Mallat, Ariane; Pawlotsky, Jean-Michel
Abstract: We assessed the broadly used, off-label combination of sofosbuvir, daclatasvir, simeprevir, and ribavirin in direct-acting antiviral–experienced patients, as recommended in current guidelines despite scarce data. After 24 weeks' treatment, sustained virological response 12 weeks after the end of treatment was achieved in 6 patients (60%). Two cirrhotic patients relapsed and 2 discontinued treatment due to serious adverse events.